Pengaruh Gaya Kepemimpinan Suportif Dan Kompensasi Terhadap Kinerja Karyawan PT BPR Majalengka Jabar Cabang Cigasong - Nur, Latief Z. Nur; Mahiri, Eli Achmad; Junaeni, Yeni (Entrepreneur: Jurnal Bisnis Manajemen dan Kewirausahaan, 2025)
High employee performance is highly expected by the company. The more employees who have high performance, the company's overall productivity will increase. One of the factors that influences performance includes a supportive leadership style and compensation provided by the company. The purpose of this research is to find out the influence of supportive leadership style and compensation on employee performance at PT BPR Majalengka Jabar Cigasong Branch. The method used in this study is a survey method with a descriptive and verification analysis approach. The population in this study were all employees of PT BPR Majalengka Jabar Cigasong Branch when the study was conducted as many as 39 employees. Using saturated sampling method, the entire population is used as a research sample. The data collection technique in this study was distributing questionnaires using a Likert scale. The data analysis used is the classical assumption test, multiple regression analysis, the coefficient of determination, model feasibility test and hypothesis testing using a partial test. The results of the study show that a supportive leadership style has no significant effect on employee performance. While compensation has a significant effect on employee performance